Seasonal distribution of phytoplankton in Orduzu Dam Lake (Malatya, Turkey) - Çetin, A. Kadri; Şen, Bülent (My University, 2004)
The species composition and seasonal distribution of phytoplankton in Orduzu Dam Lake was studied for a year. Diatoms (Bacillariophyta) were most diverse, followed by green algae (Chlorophyta), blue-green algae (Cyanophyta), euglenoids (Euglenophyta) and dinoflagellates (Dinophyta). A total of 117 taxa were recorded and the phytoplankton of the lake contained a large number of detached benthic algae. Phytoplankton assemblages were dominated by diatoms in all the periods investigated and centric diatoms were the most abundant. Overall phytoplankton density was high during the spring and summer months and the highest phytoplankton density was observed in August. The abundance of phytoplankton was positively correlated with water temperature. © TÜBITAK.
Keywords: Malatya; Orduzu Dam Lake; Phytoplankton; Seasonal variations; Turkey